Central Limit Theorem for Coloured Hard Dimers - Maria Simonetta Bernabei; Horst Thaler (Journal of Probability and Statistics)
We study the central limit theorem for a class of coloured graphs. This means that we investigate the limit behavior of certain random variables whose values are combinatorial parameters associated to these graphs. The techniques used at arriving this result comprise combinatorics, generating functions, and conditional expectations.